Impact of alcohol on hepatitis C virus replication and interferon signaling - McCartney, Erin M (Baishideng, 2010)
Hepatitis C virus (HCV) is one of the main etiological factors responsible for liver disease worldwide. It has been estimated that there are over 170 million people infected with HCV worldwide. Of these infected individuals, approximately 75% will go on to develop a life long necroinflammatory liver disease, which over decades, can result in serious complications, such as cirrhosis and hepatocellular carcinoma. Currently there is no effective vaccine and whilst antiviral therapies have been improved, they are still only effective in approximately 50% of individuals. HCV infection stands as a major cause of global morbidity and suffering, and places a significant burden on health systems. The second highest cause of liver disease in the western world is alcoholic liver disease. Frequently, HCV infected individuals consume alcohol, and the combined effect of HCV and alcohol consumption is deleterious for both liver disease and response to treatment. This review discusses the impact of alcohol metabolism on HCV replication and the negative impact on interferon (IFN)-α treatment, with a particular focus on how alcohol and HCV act synergistically to increase oxidative stress, ultimately leading to exacerbated liver disease and a reduction in the efficacy of IFN-α treatment. A better understanding of the complicated mechanisms at play in hepatocytes infected with HCV and metabolizing alcohol will hopefully provide better treatment options for chronic hepatitis C individuals that consume alcohol.